Essential Oils and their Antimicrobial Activity: A Review - Rufa’i J.M.S; Yangora, Y.M.; Usman, A.D.; Shamsuddeen, U. (UMYU Journal of Microbiology Research)
Essential oils (EOs) have been used in ethno-medicine as an effective and safe antimicrobial agents for a long time. They have been evaluated for the bactericidal, fungicidal, antiparasitical, insecticidal, virucidal, medicinal and cosmetics applications. EOs are derived from various species of edible and medicinal plants including herbs and spices. They are liquid and volatile complex mixture of compounds obtained from different parts of plants such as tea tree, oregano tree, clove, thyme, citrus and mint. Terpenes and terpenoids and their derivatives are the major constituents of EOs while aromatic and aliphatic components are the minor constituents. EOs possess strong antibacterial and antifungal properties for both susceptible and resistant strains, where they have the ability to damage the structural integrity of cell membrane, induce leakage of cell constituents, influencing the cell metabolism and eventually causing cell death.